MicroRNA-155 promotes autophagy to eliminate intracellular mycobacteria by targeting Rheb. - Jinli Wang (Public Library of Science (PLoS), 2013)
Mycobacterium tuberculosis is a hard-to-eradicate intracellular pathogen that infects one-third of the global population. It can live within macrophages owning to its ability to arrest phagolysosome biogenesis. Autophagy has recently been identified as an effective way to control the intracellular mycobacteria by enhancing phagosome maturation. In the present study, we demonstrate a novel role of miR-155 in regulating the autophagy-mediated anti-mycobacterial response. Both in vivo and in vitro studies showed that miR-155 expression was significantly enhanced after mycobacterial infection. Forced expression of miR-155 accelerated the autophagic response in macrophages, thus promoting the maturation of mycobacterial phagosomes and decreasing the survival rate of intracellular mycobacteria, while transfection with miR-155 inhibitor increased mycobacterial survival. However, macrophage-mediated mycobacterial phagocytosis was not affected after miR-155 overexpression or inhibition. Furthermore, blocking autophagy with specific inhibitor 3-methyladenine or silencing of autophagy related gene 7 (Atg7) reduced the ability of miR-155 to promote autophagy and mycobacterial elimination. More importantly, our study demonstrated that miR-155 bound to the 3'-untranslated region of Ras homologue enriched in brain (Rheb), a negative regulator of autophagy, accelerated the process of autophagy and sequential killing of intracellular mycobacteria by suppressing Rheb expression. Our results reveal a novel role of miR-155 in regulating autophagy-mediated mycobacterial elimination by targeting Rheb, and provide potential targets for clinical treatment.